Important of nutritional care in super aged society : - malnutrition, sarcopenia, and cachexia – their impact on senior’s prognosis - Naomi Nakayama (Indonesian Nutrition Association, 2022)
Japan has been facing serious aged society ahead of the world as seniors’ population has exceeded 27%. In this background, governmental policy of medical reformation has released in which expansion of home care and hospital beds reduction have promoted.